Pemberian WIUPK kepada Organisasi Kemasyarakatan Keagamaan: Analisis terhadap UU Minerba dan PP Nomor 25 Tahun 2024 - Hasibuan, Amanda Syafani Al Ikhsan; Nasution, Iwan (Universitas Muhammadiyah Ponorogo, 2025)
This study This study aims to examine the relationship between the provisions of Law Number 3 of 2020 concerning Mineral and Coal Mining (Minerba Law) and Government Regulation Number 25 of 2024, specifically regarding the mechanism for granting Special Mining Business Permit Areas (WIUPK) to religious-based community organizations. The Minerba Law explicitly prioritizes granting IUPK to State-Owned Enterprises (BUMN) and Regional-Owned Enterprises (BUMD), while private businesses can only obtain IUPK through an auction process. However, Article 83A of Government Regulation Number 25 of 2024 gives priority to business entities owned by religious organizations without an auction mechanism, even though legally these businesses are still classified as private businesses in accordance with the provisions of the Limited Liability Company Law. This provision creates regulatory disharmony that has the potential to create legal uncertainty and inequality in mining governance. This study uses a normative legal method with a statutory and conceptual approach. Preliminary findings indicate that Government Regulation No. 25 of 2024 violates the principle of lex superior derogat legi inferiori, which states that lower-level regulations must not deviate from higher-level regulations in the national legal hierarchy. Therefore, a revision of the Mineral and Coal Mining Law is needed to provide a clear and consistent legal basis, as well as strengthening the oversight system for community-owned business entities to ensure transparent, accountable, and sustainable governance practices in accordance with good governance.